Structure–phase state of the surface layers in rails subjected to differential hardening; Russian Metallurgy (Metally); Vol. 2015, iss. 13 - Gromov V. E. Viktor Evgenjevich; Glezer A. M. Aleksandr Markovich; Morozov K. V. Konstantin Viktorovich; Ivanov Yu. F. Yuriy Fedorovich; Volkov K. V. Konstantin Vladimirovich (2015, 2015)
Title screen